Compatible With Confusion: Phrasing Pitfalls in Anatomic Pathology Reports. Issue 4 (July 2022) - Findeis, Sarah K.; Huber, Aaron R.; Whitney-Miller, Christa L.
Abstract: Diagnostic uncertainty and the communication of this uncertainty is inherent in all specialties of medicine. The surgical pathology community uses a wide variety of phrases to express diagnostic uncertainty, even though there is literature that has shown use of uncertainty phrases leads to misunderstandings. We present a case that shows how uncertainty phrasing in a final diagnosis contributed to confusion surrounding patient care and resulted in sending the case for outside consultation. In addition, we review the literature surrounding uncertainty phrasing and discuss reporting of altered or amended reports.